Investigating Students’ Speaking Confidence on Al-Amin English Club (AEC) - Supriyani, Supriyani; Kunah, Kunah; Dewi, Selvia (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This study intends to investigate how students at STKIP Al-Amin Indramayu perceive the Al-Amin English Club (AEC) as a platform for learning English and how confident they are in their ability to speak the language. This study takes a qualitative approach using phenomenology. It was carried out in STKIP Al-Amin Indramayu, West Java, at the Al-Amin English Club, one of the student platforms. To gather detailed information regarding this platform, the researchers spoke with five interviewees. The sample was taken from representatives of semester two, four and six of the English education department who play an active role on this platform. Data for this study was gathered through documentation, interviews, and observation. In order to determine how this platform affects students' self-confidence, this study focuses on examining the viewpoints of Al-Amin English Club members. The findings demonstrated that the learning activities offered by Al-Amin English Club are pertinent to the growth of students' English confidence. In contrast to earlier research that concentrated more on the speaking abilities of the students, this study focuses directly on the topic of self-confidence in speaking English. This platform has a positive impact on pupils' confidence, according to their viewpoints. During this activity, students' confidence in speaking English increases. Furthermore, the encouraging friendship environment is another factor that keeps students motivated to learn English, particularly in the Al-Amin English Club. Additionally, the more laid-back and informal classroom environment encourages students to participate in the Al-Amin English Club learning process.